Влияние информационного взрыва на способность познания мира - Погорелова, Л. А. (ХНУРЕ, 2022)
The article discusses the main positive and negative aspects of the information explosion and its impact on modern society. Issues of the impact on a person of a large amount of information, as well as the impact on a person and society as a whole. At the moment, an information explosion is no less dangerous than a demographic or food explosion, because the former greatly affects the spiritual world of a person, changes his consciousness, foundations, traditions, moral values, especially among young people. What is going on in the minds of the younger generation is much more dangerous than the rapid reproduction of the population and the lack of food in the world.
Keywords: влияние информационного взрыва